Activation of adenosine A2A receptor induced interleukin-23 mRNA expression in macrophages of ankylosing spondylitis patients. (April 2020) - Akhtari, Maryam; Vojdanian, Mahdi; Javinani, Ali; Ashraf-Ganjouei, Amir; Jamshidi, Ahmadreza; Mahmoudi, Mahdi
Highlights: A2A AR agonist decreases TNF-α secretion by macrophages of AS patients. A2A AR activation increases IL23A mRNA expression by macrophages of AS patients. A2A AR activation did not have any influence on macrophages of healthy individuals. Abstract: Background: Ankylosing spondylitis (AS) is an auto-inflammatory debilitating disorder with a complex pathogenesis. The adenosinergic pathway is an immunologic regulating pathway with a potential role in AS pathophysiology. In the present study, we have aimed to investigate the influence of A2A adenosine receptor (A2A AR) activation on tumor necrosis factor-α (TNF-α) and interleukin-23 (IL-23) expression and secretion by monocyte-generated macrophages of AS patients. Methods: Whole-blood separated monocytes were extracted from 14 AS patients and 14 healthy controls. Macrophages were differentiated by macrophage colony-stimulating factor (M-CSF), and surface markers were confirmed by flow cytometer. Cells were treated with CGS-21680 as a known agonist of A2A AR. Analysis of ADORA2A, TNFA, and IL23A gene expression was performed by SYBR green real-time PCR. The concentration of secreted cytokines was also measured by ELISA kits. Results: Based on our analysis, CGS-21680 significantly decreased TNF-α secretion by monocyte-derived macrophages of AS patients. Moreover, A2A AR agonist increased the IL23A mRNA expression level in monocyte-derived macrophages of AS patients considerably. Whereas, CGS-21680 did not have any influence on macrophages of healthy individuals. Conclusion: According to our results, it appears that A2A AR activation can increase IL-23 secretion by monocyte-derived macrophages of AS patients. Although the TNF-α reducing effect of A2A AR agonists can be a potential target in AS treatment, robust increasing of IL-23 should be considered as the undesirable effect of these agents.